Análise da estabilidade de sistemas elétricos de potência usando modelos genéricos de fontes eólica e solar fotovoltaica - Parente, Deleon Ponte (2018)
The electricity generation from renewable energy sources, controlled by power electronic converters, has rapidly increased for the last few years worldwide. To properly integrate it to the power systems, the effects of renewable energy sources with variable power, such as wind power and solar power systems (PV), should be evaluated by means of stability analysis. Power systems stability is related to a sudden increase in load, generation loss, load rejection and short circuit. Thus, a complete electromechanical model, representing the dynamic coupling of electrical and mechanical phenomena and the electronic interface of the sources, is needed. This work makes use of generic models of wind power plants and photovoltaic power plant proposed by the Western Electricity Coordinating Council (WECC). The term generic models refer to non-proprietary dynamic models used to represent variable power plants, regardless of the manufacturer, with similar physical and control topology. The generic models shall provide a representation of dynamic electrical performance of power plants during grid disturbances. Such models are employed by the system operators for planning and to manage the power system, since the use of detailed manufacturer models is impractical. This dissertation aims to show the stability analysis results of variable speed wind turbines with partial scale power converter and with full-scale converter and photovoltaic systems. The generic dynamic models for PV plants includes the plant controller, electrical controls and grid interface modules, intended for large-scale PV plants, or a simplified model intended for distribution-connected, aggregated PV plants. The generic models for wind turbine includes, besides the modules mentioned, the module to represents the aerodynamic conversion, the pitch controller, the torque controller and the turbine itself. The models were designed so that they can represent the dynamics of the plants associated to a low computational cost. In this work, the effects on the transient stability in a simplified system proposed by WECC and in the 10-Machine New-England Power System IEEE benchmark are analyzed with MATLAB-Simulink R in different levels of penetration of renewable generation. The generic models used were validated by WECC and they represent real wind turbine generators and photovoltaic systems from various manufacturers. It was verified that the characteristics of the models and the control strategies performed are determinant to reduce the disturbances impact on power systems. The modeled power plants were programmed according to the Brazilian grid codes and behaved itself like according that requirements. The proposed WECC models were able to guarantee the power system stability in different fault scenarios. In these scenarios particularly with wind power penetration cases remain below 34% and with photovoltaic system below 43%, the power system maintains the stability. During the contingencies, the violation of the low voltage ride through curve due dynamic undervoltage and overvoltage was the main cause of the collapse of the power plants.